How do you simplify #(m^4n^-2)(m^2n^3)#?

1 Answer
Mar 14, 2017

Answer:

See the entire solution process below:

Explanation:

First, rewrite this expression as:

#(m^4 * m^2)(n^-2 * n^3)#

Next, use this rule of exponents to combine the terms:

#x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b))#

#(m^color(red)(4) * m^color(blue)(2))(n^color(red)(-2) * n^color(blue)(3)) = m^(color(red)(4) + color(blue)(2))x^(color(red)(-2) + color(blue)(3)) = m^6n^1#

Now, use this rule of exponents to complete the simplification:

#a^color(red)(1) = a#

#m^6n^color(red)(1) = m^6n#